Possible Role of Circulating Tumour Cells for Prediction of Salvage Lymph Node Dissection Outcome in Patients with Early Prostate Cancer Recurrence - Sophie Knipper (Elsevier, 2021)
Promising oncological results have been reported for salvage lymph node dissection (SLND) with prostate-specific membrane antigen–radioguided surgery (PSMA-RGS) in patients with prostate cancer (PCa) recurrence. We performed a proof-of-principle study assessing circulating tumour cells (CTCs) as a prognostic marker in patients undergoing SLND. Twenty consecutive patients with recurrent PCa treated with PSMA-RGS during April–July 2019 for PSMA-positive LNs were evaluated. Preoperative CTC counts were assessed using the US Food and Drug Administration–approved CellSearch system. Biochemical recurrence (BCR)-free survival (BFS) and therapy-free survival (TFS) were evaluated using the Kaplan-Meier method. Overall, three patients (15%) were CTC-positive. Postoperatively, CTC-positive patients had more pathologically positive LNs (median 8 vs 2) without a difference in overall LN count. During median follow-up of 10.1 mo, 14 patients experienced BCR and five received further therapy. In Kaplan-Meier analyses, median BFS was 1.4 versus 4.3 mo and median TFS was 10.3 mo versus not reached for CTC-positive versus CTC-negative patients. The main limitations are the small number of patients, the retrospective design, and short follow-up. Our pilot study suggests that CTC-positive patients seem to have worse pathological and short-term oncological outcomes. Therefore, further validation of this biomarker for treatment decision-making before local salvage therapy could be of value. Patient summary: We looked at outcomes for lymph node dissection in patients with recurrence of prostate cancer. We found that outcomes appear to be worse when circulating tumour cells (CTCs) can be measured in the blood preoperatively. We conclude that detection of CTCs indicates spread of tumour cells via the blood, which may limit the benefit of lymph node dissection. Thus, CTCs should be investigated in further studies as a potential marker to help in selecting patients who could benefit from lymph node dissection if their prostate cancer recurs.